Det kristne næstekærlighedsbud som etisk anti-etik - Karlsen, Mads Peter (Dansk Teologisk Tidsskrift, 2014)
The twofold aim of this article is to demonstrate (1) that a more constructive and mutually productive relationship is possible between theology and psychoanalysis, and doing this arguing (2) that psychoanalysis can assist theology understand the injunction of neighbour love as a form of ethical anti-ethics while theology can assist psychoanalysis maintain the ethical insight that there is something about human existence that is beyond the pleasure principle, something that cannot be reduced to a matter of pure survival and life sustainment, and that this constitutes a challenge for ethics. The article’s first three sections can be divided into two main parts. The first part (section 2) accounts for the criticism of the Christian variation of the injunction of neighbour love that Freud presents in Civilization and Its Discontents, and examines the background for this critique. The second part (section 3-4) encircles the concept of the neighbour as the hub of a form of ethical anti-ethics through a reading of some key passages from Jacques Lacan’s famous Seminar VII on psychoanalytic ethics and Søren Kierkegaard’s Works of Love. The article last section (section 5) provides a brief concluding summary.